2023
DOI: 10.3390/photonics10050558
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Secure Multi-Party Summation with Identity Authentication Based on Commutative Encryption

Abstract: In quantum secure multi-party summation protocols, some attackers can impersonate legitimate participants in the summation process, and easily steal the summation results from the participants. This is often overlooked for existing secure multi-party summation protocols, thus rendering them insecure. Based on commutative encryption, a quantum secure multi-party summation protocol with identity authentication is proposed in this paper. In the protocol, each participant encodes a secret integer on photons via un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Based on these principles, the MDI-QKD protocol can achieve higher security and confidentiality in quantum communication. On the contrary, due to greater instability, higher deployment costs, and lower key generation rates under the same link deployment length conditions, the keys generated by the MDI-QKD protocol are more valuable than those generated by the BB84 protocol [34].…”
Section: Qkd Protocol Model and Related Definitionsmentioning
confidence: 99%
“…Based on these principles, the MDI-QKD protocol can achieve higher security and confidentiality in quantum communication. On the contrary, due to greater instability, higher deployment costs, and lower key generation rates under the same link deployment length conditions, the keys generated by the MDI-QKD protocol are more valuable than those generated by the BB84 protocol [34].…”
Section: Qkd Protocol Model and Related Definitionsmentioning
confidence: 99%
“…In the same year, Shi et al [42] proposed device-independent secure multi-party modulo 2 summation and modulo d summation protocols based on MDI-QKD technology, using weak coherent pulses as quantum resources, and applying only simple-gate operations and Bell measurements, which have stronger practicality; Hayashi et al [43] proposed a quantum secure multi-party summation protocol based on secure modulo zero-sum randomness; Cai et al [44] pointed out that traditional secure summation protocols may suffer from impersonation attacks wherein fake data are sent by impostor parties, resulting in erroneous summation results, and proposed an improved scheme. In 2023, Wang et al [45] proposed an identity authentication method based on exchange encryption, which can solve the problem of impersonating parties in secure multi-party summation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, after quantum electrodynamics was established, it was confirmed that photons are medium particles for the transmission of electromagnetic information. Photons are often used for quantum information transmission [1][2][3][4] because of their excellent properties of easy generation and manipulation and their ability to transmit over long distances through free-space or fiber channels [5]. Therefore, It is very important and meaningful to study various applications in electronic commerce based on quantum mechanics using photons as information carriers.…”
Section: Introductionmentioning
confidence: 99%